Characterisation of an under-cured epoxy adhesive for use on the riv-bonded Bloodhound SSC lower chassis - Ben Evans (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications, 2015)
Bloodhound SSC is a vehicle that aims to raise the World Land Speed Record to over 1000 mile/h in Hakskeen Pan, South Africa. Its lower chassis is a riv-bonded fabrication made using steel sheet for skins and aluminium alloy machinings for bulkheads. Fasteners alone were enough to satisfy the lower chassis structural requirements; however, Redux 312/5 epoxy adhesive was used to increase the stiffness of the structure and limit potential corrosion due to water and soil ingress. The use of dissimilar metals in the chassis could lead to panel buckling during elevated cure temperatures, meaning a low adhesive cure temperature of 80–90 ℃ was required to minimise this risk. As the cure pressure for the lower chassis adhesive was achieved using only rivets, the variation of cure pressure was experimentally investigated and found to be within the manufacturer’s recommendations for large sections of the lower chassis. Tensile testing indicated the chassis could be cured at 80 ℃ instead of the optimum 121 ℃, without significant loss of mechanical strength. A thermal characterisation of the adhesive was conducted using dynamic mechanical analysis and differential scanning calorimetry. A variety of cure profiles was investigated and resulted in a cure profile that maximised the glass transition temperature (Tg). An increase in cure duration to 8 h was recommended, which resulted in an increase in Tg by 15–24 ℃ to 83–92 ℃.